2021
DOI: 10.1097/sla.0000000000005079
|View full text |Cite
|
Sign up to set email alerts
|

Aligning Patient Acuity With Resource Intensity After Major Surgery

Abstract: Objective: Develop unifying definitions and paradigms for data-driven methods to augment postoperative resource intensity decisions. Summary Background Data: Postoperative level-of-care assignments and frequency of vital sign and laboratory measurements (ie, resource intensity) should align with patient acuity. Effective, data-driven decision-support platforms could improve value of care for millions of patients annually, but their development is hindered by the lack of salient definitions and paradigms. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…The best approach is controversial, due to resource limitations, 7 mixed evidence of efficacy of ICU admission, 8,9 a lack of evidence of efficacy of HDU care, 10 and difficulties triaging patients to avoid overuse of ICU resources. 11 Ward-based care with MET rescue in the event of physiological deterioration is the most common strategy used in Australian hospitals, as MET systems reduce mortality for surgical patients. 12,13 However, recent evidence suggested that high-risk patients were more likely to die if their admission to ICU after surgery occurred following a MET call compared with immediate admission to ICU, suggesting that preventing deterioration of physiology was preferable to delayed rescue via MET call.…”
Section: Introductionmentioning
confidence: 99%
“…The best approach is controversial, due to resource limitations, 7 mixed evidence of efficacy of ICU admission, 8,9 a lack of evidence of efficacy of HDU care, 10 and difficulties triaging patients to avoid overuse of ICU resources. 11 Ward-based care with MET rescue in the event of physiological deterioration is the most common strategy used in Australian hospitals, as MET systems reduce mortality for surgical patients. 12,13 However, recent evidence suggested that high-risk patients were more likely to die if their admission to ICU after surgery occurred following a MET call compared with immediate admission to ICU, suggesting that preventing deterioration of physiology was preferable to delayed rescue via MET call.…”
Section: Introductionmentioning
confidence: 99%
“…Human decision-making is subject to cognitive biases, errors, and preventable harm, especially for less experienced and sleep-deprived surgeons 2–7. In contrast, artificial intelligence models can rapidly and reproducibly process large quantities of data, are not susceptible to fatigue, and occasionally demonstrate superior performance in prediction and classification tasks that underlie decisions 8,9. Unlike traditional, rule-based inference engines, artificial intelligence models can discover new and complex, nonlinear associations and often outperform rule-based models 10,11.…”
mentioning
confidence: 99%
“…6 Despite the potential consequences of postoperative overtriage, there is no consensus definition of overtriage and there is sparse evidence associating overtriage, patient outcomes, and value of care. 7 Triage patterns reported in medical and mixed-medical surgical populations may not be generalizable to postoperative patients, who are uniquely vulnerable to hemorrhage, respiratory failure, opiate toxicity, and sepsis. [8][9][10] Most systems for classifying patient acuity would require further gains in accuracy and integration with clinical and digital workflows before real-world implementation.…”
mentioning
confidence: 99%